Improved Feedstock Option or Invasive Risk? Comparing Establishment and Productivity of Fertile Miscanthus × giganteus to Miscanthus sinensis - Catherine L. Bonin; Evans Mutegi; Allison A. Snow; Maria Miriti; Hsiaochi Chang; Emily A. Heaton (BioEnergy Research, 2017)

Human impacts and aridity differentially alter soil N availability in drylands worldwide - Manuel Delgado‐Baquerizo; Fernando T. Maestre; Antonio Gallardo; David J. Eldridge; Santiago Soliveres; Matthew A. Bowker; Ana Prado‐Comesaña; Juan Gaitán; José L. Quero; Victoria Ochoa; Beatriz Gozalo; Miguel García‐Gómez; et al. (Global Ecology and Biogeography, 2016)
Aims Climate and human impacts are changing the nitrogen ( N ) inputs and losses in terrestrial ecosystems. However, it is largely unknown how these two major drivers of global change will simultaneously influence the N cycle in drylands, the largest terrestrial biome on the planet. We conducted a global observational study to evaluate how aridity and human impacts, together with biotic and abiotic factors, affect key soil variables of the N cycle. Location Two hundred and twenty‐four dryland sites from all continents except A ntarctica widely differing in their environmental conditions and human influence. Methods Using a standardized field survey, we measured aridity, human impacts (i.e. proxies of land uses and air pollution), key biophysical variables (i.e. soil pH and texture and total plant cover) and six important variables related to N cycling in soils: total N , organic N , ammonium, nitrate, dissolved organic:inorganic N and N mineralization rates. We used structural equation modelling to assess the direct and indirect effects of aridity, human impacts and key biophysical variables on the N cycle. Results Human impacts increased the concentration of total N , while aridity reduced it. The effects of aridity and human impacts on the N cycle were spatially disconnected, which may favour scarcity of N in the most arid areas and promote its accumulation in the least arid areas. Main conclusions We found that increasing aridity and anthropogenic pressure are spatially disconnected in drylands. This implies that while places with low aridity and high human impact accumulate N , most arid sites with the lowest human impacts lose N . Our analyses also provide evidence that both increasing aridity and human impacts may enhance the relative dominance of inorganic N in dryland soils, having a negative impact on key functions and services provided by these ecosystems.

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

Spatial patterns of mortality in a Colorado desert plant community - Maria N. Miriti; Henry F. Howe; S. Joseph Wright (Plant Ecology, 1998)